2016
DOI: 10.1007/s12262-016-1459-0
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Injuries to the Abdomen: a Single Institutional Experience with Review of Literature

Abstract: Penetrating abdominal trauma forms an important component of surgical emergencies, most of the victims being young aged in the prime of their life. Over the past century, the diagnosis and management of this common problem has seen drastic changes, finally reaching the destination of . We present our experience in the management of this group of patients in the rural setup. This is a prospective observational study done at our hospital between 1 April 2013 and 31 March 2015 including patients who presented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
(24 reference statements)
1
11
0
1
Order By: Relevance
“…Small bowel is the most common organ injured in penetrating abdominal trauma. 4 In a study by Arslan et al, the ileum was the most common organ involved in pediatric penetrating abdominal trauma. Almost 48 % of the cases with bowel perforation did not have air under the diaphragm on standing abdominal X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…Small bowel is the most common organ injured in penetrating abdominal trauma. 4 In a study by Arslan et al, the ileum was the most common organ involved in pediatric penetrating abdominal trauma. Almost 48 % of the cases with bowel perforation did not have air under the diaphragm on standing abdominal X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…The preferred surgical methods are primary repair for minor injuries and limited bowel resection with primary anastomosis (preserving bowel length) for more extensive ones 31 . Small bowel ostomy is generally to be considered as a secondary option especially in light of complications that ensue from its high output 32 .…”
Section: Discussionmentioning
confidence: 99%
“…La técnica quirúrgica descrita para las lesiones leves es el reparo primario y para las severas la resección y anastomosis 31 . Generalmente, la ostomía no es una opción, dado a su asociación con complicaciones de fugas intestinales de alto gasto 32 .…”
Section: Discussionunclassified
“…Penetrating abdominal injuries are a frequent emergency and may cause considerable troubles at emergency service [11]. Karamercan et al [12] concluded that approximately 10% of all trauma-related deaths occurred as a result of blunt or penetrating abdominal injuries.…”
Section: Discussionmentioning
confidence: 99%